2020
DOI: 10.1051/e3sconf/202019405051
|View full text |Cite
|
Sign up to set email alerts
|

Site selection for EVCSs by GIS-based AHP method

Abstract: As an alternative to fossil-fuelled vehicles, electric vehicles (EVs) are eco-friendly which can reduce carbon emissions and improve energy efficiency. However, there are still some barriers to the development of EVs. One of the main problems is lacking scientific planning of charging stations considering social, technological and environmental factors. To solve the problem, our paper proposes a Geographic Information System (GIS)-based AHP method to find optimal locations of electric vehicle charging stations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…To meet the charging demands of diverse EV users across the country, it is essential to ensure the preservation of service capability [35]- [37]. Additionally, strategically allocating PEVCS at research and education institutions can play a vital role in fostering EV adoptions, particularly among the educated populace [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the charging demands of diverse EV users across the country, it is essential to ensure the preservation of service capability [35]- [37]. Additionally, strategically allocating PEVCS at research and education institutions can play a vital role in fostering EV adoptions, particularly among the educated populace [38].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the placement of PEVCS in park areas not only provides quick access for electric vehicle (EV) users, but also stimulates the adoption of sustainable mobility practices within recreational and social areas. Also, the high concentration of vehicles in parking garages positions them as a prime destination for EV users [38], [46], [47], [53]- [57].…”
Section: Resultsmentioning
confidence: 99%
“…However, recent attempts by researchers involve the application of GIS with MCDM AHP, FAHP, and TOPSIS techniques with the consideration of various criteria, including social, technological, environmental, geographical, economically, urbanity, transportation, energy, and so many other factors. According to the previous researchers who used the examined publications as their source, this strategy demonstrated that it gave advantages and benefits to support the adoption of EVs in many nations with EV adoption policies, a GIS-based MCDM method identified an appropriate location for EVCS to maximize their effectiveness and hasten the growth and acceptance of EVs [29]. According to [30] the method is very helpful for urban planners, decision-makers, and researchers who are designing EV charging infrastructure to encourage the adoption of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Users may find patterns, comprehend trends, keep track of changes, and react to events by being able to clearly represent various forms of data, which helps users make better decisions. Supply chain management, facilities management, environment and natural resource management, transportation, insurance, forestry, urban planning, land information system, engineering, street network, and many more industries are just a few of the many industries where it has a wide range of applications [10]. GIS has the following advantages (table 1).…”
Section: Geographic Information Systems (Gis) and Its Applicationsmentioning
confidence: 99%
“…[9], [12], [13], [21], [24], [26], [33] Distance of water resources PEVCS installation may have a bad impact on water resources. Thus, PEVCS should be located away from water sources.…”
Section: Environment Electromagnetic Interferencementioning
confidence: 99%